2023
DOI: 10.22460/infinity.v12i2.p323-338
|View full text |Cite
|
Sign up to set email alerts
|

The profile of students' mathematical representation competence, self-confidence, and habits of mind through problem-based learning models

Ahmad Ahmad,
Lukmanul Akhsani,
Zulkifley Mohamed

Abstract: Mathematics is an essential subject for students. Teachers, therefore, need to provide innovative learning that develops students' mathematical skills. This study was conducted to determine the effect of a problem-based learning (PBL) model on students' mathematical representation competencies, self-confidence, and habits of mind. It used a quantitative methodology and was conducted on eighth-grade students divided into an experimental class with a PBL model and a control class with a direct learning model. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
(49 reference statements)
0
0
0
Order By: Relevance
“…9, No. 4, April 2024 2262 learning mathematics (Ahmad et al, 2023;Hendriana et al, 2022). Research has shown that students with a high interest in mathematics have better academic achievements (Samuel & Warner, 2021;Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…9, No. 4, April 2024 2262 learning mathematics (Ahmad et al, 2023;Hendriana et al, 2022). Research has shown that students with a high interest in mathematics have better academic achievements (Samuel & Warner, 2021;Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%